2020
DOI: 10.3390/coatings10060596
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Behavior of Textured Electrosurgical Electrode in an Electric Cutting Process

Abstract: Soft tissue adhesion on the electrosurgical electrode has been a major concern in clinical surgery. In order to improve the adhesion property of the electrode, micro-textures with different morphologies including micro-dimples, longitudinal micro-channels, and lateral micro-channels were created on the electrode surface by laser surface texturing (LST). Electric cutting experiments were then performed to investigate the adhesion behavior of different electrodes. Experimental results showed that the textured el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…Альтернативным подходом к модифицированию электрохирургического инструмента стало структурирование поверхности с целью улучшения антипригарных свойств. В данном случае на поверхности предварительно формируются упорядоченные структуры, представляющие собой микроканалы или углубления [40], либо повышается шероховатость на уровне наноструктур [41,42]. Так, формирование на поверхности электрохирургического ножа из нержавеющей стали марки 304 микроканалов, перпендикулярных оси инструмента, шириной 50 мкм и глубиной 12 мкм, позволило снизить адгезию тканей за счет снижения рабочей температуры со 116 °C (не структурированная поверхность) до 93 °C [40].…”
Section: микротекстурирование поверхностиunclassified
See 1 more Smart Citation
“…Альтернативным подходом к модифицированию электрохирургического инструмента стало структурирование поверхности с целью улучшения антипригарных свойств. В данном случае на поверхности предварительно формируются упорядоченные структуры, представляющие собой микроканалы или углубления [40], либо повышается шероховатость на уровне наноструктур [41,42]. Так, формирование на поверхности электрохирургического ножа из нержавеющей стали марки 304 микроканалов, перпендикулярных оси инструмента, шириной 50 мкм и глубиной 12 мкм, позволило снизить адгезию тканей за счет снижения рабочей температуры со 116 °C (не структурированная поверхность) до 93 °C [40].…”
Section: микротекстурирование поверхностиunclassified
“…В данном случае на поверхности предварительно формируются упорядоченные структуры, представляющие собой микроканалы или углубления [40], либо повышается шероховатость на уровне наноструктур [41,42]. Так, формирование на поверхности электрохирургического ножа из нержавеющей стали марки 304 микроканалов, перпендикулярных оси инструмента, шириной 50 мкм и глубиной 12 мкм, позволило снизить адгезию тканей за счет снижения рабочей температуры со 116 °C (не структурированная поверхность) до 93 °C [40]. Придание наношероховатости поверхности электрода с помощью обработки фемтосекундным лазером поверхностного слоя толщиной 0,5 мкм также приводило к уменьшению степени адгезии ткани за счет снижения рабочей температуры с 170,48 °C до 148,45 °C [41].…”
Section: микротекстурирование поверхностиunclassified
“…Inspired by surface textures of both animals and plants in nature, many studies have explored numerous textures to enhance the antiadhesion properties of metal surfaces and cutting tools , in surgery. Zhang et al prepared a liquid-infused surface for antiadhesion, which mimicked nepenthes, but the method tended to involve many chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the fine and small working tip of the BET, it is difficult to precisely construct rough structures by a physical method on its tiny working tip . Chemical reagents or electrochemical etching may be suitable for tiny working areas, whereas the structures fabricated by them are irregular and uncontrollable. Recently, laser texturing is emerging as a controllable and efficient method to precisely construct microstructures through melting and vaporization mechanisms without using chemical reagents. Zhou et al reported that the microstructures could effectively alleviate the tissue adhesion on the electrode because of the effect of the air layer in the microtextures . Therefore, it may effectively reduce tissue adhesion in electrosurgery by applying laser texturing on irregularly shaped BETs to construct microstructures and prepare superhydrophobic BETs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, auxiliary devices, including thermal management systems and ultrasonic vibration units, increase the size or weight of surgical electrodes, thereby affecting operability. Although coatings are widely used in various medical devices, their antiadhesive effects at high temperatures have certain limitations. ,, The original intention of constructing surface microstructures is to minimize the contact area between the electrode and biological tissue, , thus achieving a reduction in adhesion. However, this antiadhesive effect is random and does not reach the ideal state because the chemical properties of the electrode surface do not change.…”
Section: Introductionmentioning
confidence: 99%